Progressive histological and behavioral deterioration of a novel mouse model of secondary hydrocephalus after subarachnoid hemorrhage - Xuehai Deng; Jianlin Ding; Chang Liu; Zhong Wang; Junchi Wang; Qiyue Duan; Weida Li; Xinlong Chen; Xiaoping Tang; Long Zhao (Scientific Reports)
Abstract Hydrocephalus commonly occurs after subarachnoid hemorrhage (SAH) and is associated with increased morbidity and disability in patients with SAH. Choroid plexus cerebrospinal fluid (CSF) hypersecretion, obliterative arachnoiditis occluding the arachnoid villi, lymphatic obstruction, subarachnoid fibrosis, and glymphatic system injury are considered the main pathological mechanisms of hydrocephalus after SAH. Although the mechanisms of hydrocephalus after SAH are increasingly being revealed, the clinical prognosis of SAH still has not improved significantly. Further research on SAH is needed to reveal the underlying mechanisms of hydrocephalus and develop translatable therapies. A model that can stably mimic the histopathological and neuroethological features of hydrocephalus is critical for animal experiments. There have been fewer animal studies on hydrocephalus after SAH than on other stroke subtypes. The development of a reproducible and effective model of hydrocephalus after SAH is essential. In this study, we establish a mouse model of SAH that stably mimics brain injury and hydrocephalus after SAH through injections of autologous blood into the cisterna magna via different methods and characterize the model in terms of neurological behavior, histology, imaging, neuronal damage, and white matter damage.